The effect of mindfulness-based interventions on educational stress, exam anxiety, and coping strategies in nursing students - Esmaeilzadeh, Samineh; Akalpler, Özlem; Evren, Duygu Oktay (Intelektual Pustaka Media Utama, 2026)
The aim of this study is to examine the effect of mindfulness-based stress reduction intervention on educational stress and coping with exam anxiety and mindfulness in nursing students. This study utilizes a quasi-experimental design with the pretest-post-test control group. Personal information form, nursing education stress scale (NESS), state test anxiety scale (STAS), and mindful attention awareness scale (MAAS) were employed as data collection instruments in the study. The study group of the research consisted of 68 students in university. Findings indicated statistically significant differences between the changes in the participant’s scores in the control and experimental groups in the overall NESS in the post-test and the application stress and academic stress scale. The results further found a statistically significant difference between the changes in the scores of the participants in the control and experimental groups in the post-test from the MASS. The intervention based on mindfulness stress reduction led to positive results in students’ coping with exam anxiety. Educational programs should be organized to enable students to cope more effectively with the stressors they encounter. Therefore, it is believed that it would be appropriate to introduce similar programs in the education process of nursing students.